International education in natural resource engineering and the KSU / EI Purpan AREM partnership - Sloan, Hale C. (Kansas State University, 2010)
The need for globally mobile and culturally intelligent engineers to address global natural resource issues is high. Current economic, political and environmental states demand that educational institutions equip engineers with diverse problem solving skill sets. International education experience is the best way for students from varied backgrounds to appreciate differences around the world, develop skill sets for global issues and operate in a multinational environment. International education programs exist between many different educational institutions. A multidisciplinary program, Agricultural Resources and Environmental Management (AREM), currently exists between Kansas State University Manhattan, Kansas, USA and Ecole d’Ingénieurs Purpan Toulouse, France. AREM is a Master’s level program designed to promote the exchange of ideas, faculty, and students in sustainable agricultural development. This program operates independently at each institution and features two courses, revolving around agro-ecological, economic, and social factors, which are co-taught via live video conference. The main objectives of this research were to compare the structural education components of engineering institutes EI Purpan and KSU in order to evaluate the efficacy and importance of the AREM program in global terms, to create a mutual understanding of program obstacles, to highlight the benefits and strengths of each institution, and to provide a common plane for forward progress. Comparisons of accreditation programs, pedagogy and curriculums at the Bachelor’s and Master’s level were conducted. The similarities and differences of the AREM program from both French and American perspectives were explored to develop recommendations for forward progress. Learning outcomes set by accreditation bodies were very similar, but the method of achieving those outcomes was dissimilar. Many differences were found in the amount of time spent on certain educational topics within the engineering curriculum. Engineering students at EI Purpan received a more rounded education, with an agricultural business management focus, enhanced with practical education through required internships. KSU engineering students received a much more technical and theoretical education based in math, physics and engineering design. Pedagogy contrasted most between schedule and on job training. Differences in Master’s degree specialization were limited, but influential. The AREM program is a specialized degree pathway at EI Purpan, while at KSU it is a graduate certificate program. At EI Purpan the AREM program is heavily advertised, while at KSU it is not. Departmental structure of American universities provides challenges to multidisciplinary programs like AREM. The strengths of each institution, practical or theoretical, should be integrated to enhance the AREM program outcomes. Possibilities exist for the AREM program to maintain its current state with minor enhancements, develop into a short summer exchange program between KSU and EI Purpan, or evolve into a joint Master’s degree. The AREM program exposes students to international collaboration, appreciation of different approaches to problems solving, and cultural eccentricities. Engineering students who participate in the AREM program are equipped to solve natural resource issues at the global scale. Improvements to the program will increase student ability and institutional reputability.
Keywords: Engineering; Education; AREM; Natural Resources; International; Engineering, Environmental (0775)